The rise of low-cost sensing for managing air pollution in cities. (February 2015) - Kumar, Prashant; Morawska, Lidia; Martani, Claudio; Biskos, George; Neophytou, Marina; Di Sabatino, Silvana; Bell, Margaret; Norford, Leslie; Britter, Rex
Abstract: Ever growing populations in cities are associated with a major increase in road vehicles and air pollution. The overall high levels of urban air pollution have been shown to be of a significant risk to city dwellers. However, the impacts of very high but temporally and spatially restricted pollution, and thus exposure, are still poorly understood. Conventional approaches to air quality monitoring are based on networks of static and sparse measurement stations. However, these are prohibitively expensive to capture tempo-spatial heterogeneity and identify pollution hotspots, which is required for the development of robust real-time strategies for exposure control. Current progress in developing low-cost micro-scale sensing technology is radically changing the conventional approach to allow real-time information in a capillary form. But the question remains whether there is value in the less accurate data they generate. This article illustrates the drivers behind current rises in the use of low-cost sensors for air pollution management in cities, while addressing the major challenges for their effective implementation. Graphical abstract: Highlights: Impacts on the health of city dwellers due to high air pollution exposure are unknown. Conventional sparse monitoring stations are unable to identify pollution hotspots. Low-cost micro-scale sensing allows capturing real-time high-grained pollution data. Fundamental drivers behind the rise of low-cost sensing and challenges are discussed.